2014
DOI: 10.1007/s10518-014-9675-0
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table tests on a three-arch type subway station structure in a liquefiable soil

Abstract: A series of large-scale shaking table tests were performed to investigate the damage mechanisms of a three-arch type subway station structure in a liquefiable soil experiencing strong motions. Methods to measure the displacement included the vision-based displacement test and the fiber Bragg grating test to measure the strain of the galvanized steel wire. Sand boils, waterspouts, ground surface cracks and settlements, and buoyancy movement of the model structure were observed. When the peak excess pore pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…e testing input excitations were 1, 3, and 5 Hz sine waves. Based on the calibration relationship, approximately 45.2 pixels represent 1 cm of actual space [22].…”
Section: Vision-based Testing Methods and Processing Methodmentioning
confidence: 99%
“…e testing input excitations were 1, 3, and 5 Hz sine waves. Based on the calibration relationship, approximately 45.2 pixels represent 1 cm of actual space [22].…”
Section: Vision-based Testing Methods and Processing Methodmentioning
confidence: 99%
“…table test [10,11,13] Shaking Table 4. Based on the analysis of the stratum of Shanghai Metro, Yang et al [4] established the shaking table test of double-deck and three-span metro station, and obtained the time-history of acceleration, structural stress, and soil surface deformation of the model; Chen et al [7,20,21] conducted a large shaking table test on liquefiable sand foundation in Nanjing, the reaction law of pore water pressure and acceleration response of the model were analysed; Bian et al [5] carried out shaking table test of geological conditions in Beijing area, analyzed the time-history of dynamic stress, and studied the acceleration and stress distribution in different positions of the metro station; Cheng et al [34] conducted the shaking table test of three-layer metro station, obtained the conclusion that failure of multi-layer metro station was controlled by displacement and improving the ductility of the structure was an effective method to improve the seismic performance of the underground structure.…”
Section: Fig 11 -Earthquake Damage Of Dakai Metro Station and Destrumentioning
confidence: 99%
“…Wang [17], Zhuang [18], and Li et al [19] used FEM to establish numerical model for metro station in soft soil, and analysed the seismic response and failure mechanism of metro station with different depths, layers and structures. For comprehensive analysis, Chen [20,21] and Moghadam et al [22] carried out shaking table test and used FEM to establish numerical model for test, compared the results of shaking table test and numerical simulation, and studied the seismic response of metro station deeply. These studies are based on structural dynamics, mainly study the seismic responses of the columns and some structures of metro station, and do not analyse the difference between the seismic response of metro station with different structures, so there is no systematic and comprehensive analysis of the earthquake response of the island platform metro station.…”
Section: Introductionmentioning
confidence: 99%
“…Dashti et al carried out a series of liquefaction model tests of low-rise buildings through the centrifuge shaking table test; the mechanism of building settlement that was caused by liquefaction was discussed [20]. Chen et al studied the dynamic characteristics and damage law of subway station [21]. Other scholars have also undertaken a lot of research on the dynamic response of various structures and foundations under earthquake using shaking table test and found that the depth and compactness of soil, the existence of structures, and the input parameters of shaking excitation have obvious effects on site liquefaction and dynamic response of structures and soil [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%